A comparison between robotic, laparoscopic and open hepatectomy: A systematic review and network meta-analysis. Issue 7 (July 2020) - Gavriilidis, Paschalis; Roberts, Keith J.; Aldrighetti, Luca; Sutcliffe, Robert P.
Abstract: Background: The evidence of pairwise meta-analysis of Robotic Hepatectomy (RH) vs Laparoscopic Hepatectomy (LH) and RH vs Open Hepatectomy (OH) is inconclusive. Therefore, the aim of this study, was to compare the outcomes of RH, LH and OH by performing a network meta-analysis. Methods: A systematic literature search was performed in the following databases: Pubmed, Google scholar, EMBASE and Cochrane library. Cost-effectiveness and survival benefits were selected as primary outcomes. Results: The cost was less in OH compared to both minimally invasive procedures, LH demonstrated lower cost compared to RH, but the differences were not statistically significant. Both the RH and LH cohorts demonstrated significantly lower estimated blood loss, reduced major morbidity rate and shorter length of stay compared to OH cohort. The LH and OH cohorts demonstrated significantly shorter operative time and duration of clamping compared to the RH cohort. The LH cohort included significantly smaller tumours compared to the OH cohort. Conclusion: The present network meta-analysis, demonstrated that both RH and LH in malignant and benign conditions were associated with lower morbidity rates, shorter hospital stay and the procedure related costs were statistically nonsignificant between RH, LH and OH.